Peningkatan Kemampuan Berpikir Kritis Peserta Didik Melalui Model Problem Based Learning dalam Pembelajaran IPS Pada Siswa Kelas VIII di MTs Ddi Al-Amin - Ernawati, Ernawati; Yahya, Muh.; Rismawanti, Erni; Taskirah, Andi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims 1) To determine students' activities using the problem-based learning model in class VIII social studies learning at MTs DDI AL-AMIN. 2) To improve students' critical thinking skills by using the problem-based learning model in class VIII learning at MTs DDI AL-AMIN. This research is classroom action research (PTK) by carrying out 3 cycles, in each cycle there are 4 stages, namely planning, action, observation and reflection. The subjects of this research were class VIII students consisting of 16 students. Data sources obtained from students and teachers. Data collection techniques used were observation, tests and documentation, qualitative and quantitative data analysis techniques. Based on the research results, it shows that (1) the implementation of the problem-based learning model to improve students' critical thinking skills in cycle I analyzed the images presented, in cycle II used TTS in learning, cycle III used PPT material and learning videos then made mind mapping. (2) in cycle I for the pretest and posttest it reached 14%, then in cycle II it increased to 43% and in cycle III the percentage of completion reached 91% or overall students had reached the KKM.